2014
DOI: 10.1061/(asce)he.1943-5584.0000878
|View full text |Cite
|
Sign up to set email alerts
|

Extreme Rainfall Nonstationarity Investigation and Intensity–Frequency–Duration Relationship

Abstract: Non-stationary behaviour of recent climate increases concerns amongst hydrologists about the currently used design rainfall estimates. Therefore, it is necessary to perform analysis to confirm stationarity or detect non-stationarity of extreme rainfall data in order to derive accurate design rainfall estimates for infrastructure projects and flood mitigation works.Extreme rainfall non-stationarity analysis of the storm durations from 6 min to 72 hours was conducted in this study using data from the Melbourne R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
68
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 111 publications
(77 citation statements)
references
References 47 publications
1
68
0
Order By: Relevance
“…We argue that although it is crucial to recognize nonstationarity in precipitation extremes, the stationary form of IDFs can still represent the extreme rainfall statistics for the present-day climate over the Southern Ontario region. Our results are consistent with Yilmaz et al (2014) and Yilmaz and Perera (2013), in which authors found despite the presence of (statistically) significant trends in rainfall extremes; nonstationary GEV models did not show any additional advantages over the stationary models. As supported by the previous study (Singh et al, 2016), we attribute that the little or no changes in extreme rainfall statistics in the urbanized setting is due to the stabilization of urban development leading to no substantial variations in the land use pattern.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…We argue that although it is crucial to recognize nonstationarity in precipitation extremes, the stationary form of IDFs can still represent the extreme rainfall statistics for the present-day climate over the Southern Ontario region. Our results are consistent with Yilmaz et al (2014) and Yilmaz and Perera (2013), in which authors found despite the presence of (statistically) significant trends in rainfall extremes; nonstationary GEV models did not show any additional advantages over the stationary models. As supported by the previous study (Singh et al, 2016), we attribute that the little or no changes in extreme rainfall statistics in the urbanized setting is due to the stabilization of urban development leading to no substantial variations in the land use pattern.…”
Section: Discussionsupporting
confidence: 92%
“…Nevertheless, the methodology to derive existing IDF curves has certain drawbacks, for example that the current IDF curves in Canada are based on the assumption of stationarity, which implies that statistical properties of hydroclimatic time series will remain the same over the period of time. However, the impact of urbanization and humaninduced climate change (IPCC SREX, 2012;Villarini et al, 2009a;Milly et al, 2009;Kunkel, 2003) raises the question of whether the stationarity assumption to derive IDF curves is still reliable for urban infrastructural planning (Sarhadi and Soulis, 2017;Cheng and AghaKouchak, 2014;Jakob, 2013;Yilmaz et al, 2014a;Yilmaz and Perera, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Jakob et al (2011a, b) investigated the potential effects of climate change and variability on rainfall intensityfrequency-duration (IFD) relationships in Australia, considering possible non-stationarity of extreme rainfall data in design rainfall estimates. Yilmaz and Perera (2014) developed stationary and non-stationary GEV models using a single station in Melbourne considering data for storm durations ranging from 6 min to 72 h to construct IFD curves through frequency analysis. They investigated the advantages of nonstationary models over stationary ones using graphical tests.…”
Section: A G Yilmaz Et Al: Climate Change and Variability On Rainfmentioning
confidence: 99%
“…Expected rainfall intensities for return periods of 2, 5, 10, 20, 50 and 100 years were derived and compared for two time slices : 1925-1966 (i.e. cooler period) and 1967-2010 (warmer period) after selecting 1967 as the change point based on the findings of Yilmaz and Perera (2014). Yilmaz and Perera (2014) conducted the change point analysis for extreme rainfall data for storm durations ranging from 6 min to 72 h in Melbourne, and stated that the year 1966 is the change point.…”
Section: A G Yilmaz Et Al: Climate Change and Variability On Rainfmentioning
confidence: 99%
See 1 more Smart Citation